Update on Molecular Pathology of Cutaneous Melanocytic Lesions: What is New in Diagnosis and Molecular Testing for Treatment? - van Engen-van Grunsven, Adriana C. H.; Kusters-Vandevelde, Heidi; Groenen, Patricia J. T. A.; Blokx, Willeke A. M. (Frontiers in Medicine, 2014)
In this article we give an update on recent findings regarding molecular pathology in cutaneous melanocytic tumours. The focus lies on use of genetics in the diagnosis of distinct subtypes of spitzoid tumours that are often characterized by specific phenotypic-genotypic alterations that can frequently be recognized by adequate histological examination. Typical illustrating cases are given in order to increase recognition of these lesions in daily dermatopathology practice. New molecular findings in the pathogenesis of congenital melanocytic tumours and neurocutaneous melanosis are reviewed. In addition use of mutation analysis in the differential diagnosis of melanoma metastasis is discussed. Finally application of mutation analysis in targeted therapy in advanced melanoma with advantages of new techniques such as next generation sequencing is described.